Inventarisasi Jenis-jenis Tumbuhan yang dapat Digunakan sebagai Bahan Praktikum Sistem Transportasi pada Tumbuhan - Hartono (Bionature, 2009)
This descriptive study aims to do inventarisation of some variety of plants which could be used as material in the practical work of transportation system in plants. The study was done in four phases; exploration of plants in the natural environment, the test of the plants in Natural Science Laboratory of SMPN 27 Makassar, determination of the plants which could be used as practical material in transportation system based on the laboratory test, and “fit and proper” test of the plants used in the experiment which was done by the students of SMPN 27 Makassar. The study showed that there were 9 species out of 25 variety of plants explored in natural environment that could be used in the plants transportation system experiment in laboratory. Those species are Piperomia pellucida (L.)H.B.K., Amaranthus gracilis Desf., Celosia arganteaL., Physalis angulata L., Lycopersicon lycopersicum (L.) Karsten, Coleus sp., Coleus swisssunshine, Helianthus annuus L., dan Cleome gynandra L.